Biological aspects of pink ear emperor, Lethrinus lentjan (Lacepede, 1802) in Bangka and adjacent waters - Yoke Hany Restiangsih; Nur’ainun Muchlis (Jurnal Iktiologi Indonesia, 2019)
Coral fish is the one of the important fish resources in Indonesian waters, but the potential and exploitation rate needs to be obtained. Pink ear emperor is one of coral fish that many caught in Bangka. Research was conducted to determine biological aspect of pink ear emperor caught by fish traps, that includes length distribution, length-weight relationship, sex ratio, maturity stage, food habits, and length at first mature. This research was conducted from February 2014 to November 2015 with sampling location in Sungailiat fishing port. The observed aspects included fork length, weight, sex, gonad maturity and fish stomach contents was done monthly. The results showed the growth pattern are allometric negative, folk length ranged from 12 to 58 cm. The condition of sex ratio of males to females was 1:2,06. The gonade maturity stage of males and females were stage I, II, III, and IV for all months of observation. Stomach contained was shellfish, crap, shrimp and fish. Length at first capture(Lc) was 28 cm and length at first maturity(Lm) was 26 cm. Size length at first capture was bigger than the size length at first maturity, so the pink ear emperor at Sungailiat available to maintained the balance of fish stock on population. Abstrak Ikan karang merupakan salah satu sumber daya yang penting di perairan Indonesia, namun tingkat potensi dan tingkat pemanfaatannya masih perlu untuk dikaji. Ikan lencam merupakan salah satu ikan karang yang banyak tertangkap di perairan Bangka. Tujuan penelitian ini mengkaji beberapa aspek biologi ikan lencam hasil tangkapan bubu, meliputi sebaran ukuran panjang, pola pertumbuhan, nisbah kelamin, dan ukuran rata-rata pertama kali matang gonad dan kebiasaan makan. Penelitian ini dilaksanankan di PPN Sungailiat pada bulan Februari 2014 – November 2015. Aspek yang diamati meliputi panjang cagak, bobot tubuh ikan, jenis kelamin, kematangan gonad, dan isi lambung ikan. Hasil penelitian menunjukkan pola pertumbuhan ikan lencam bersifat allometrik negatif. Sebaran ukuran panjang berkisar antara 12 – 58 cm. Nisbah kelamin jantan terhadap betina sebagai 1 : 2,06. Pada setiap bulan pengamatan tingkat kematangan gonad jantan dan betina berada pada stadia I, II, III, dan IV. Isi lambung ikan lencam selama pengamatan terdiri dari kerang-kerangan, kepiting, udang, dan hancuran ikan. Panjang pertama kali ikan tertangkap (Lc) sebesar 28 cm dan pertama kali matang gonad (Lm) sebesar 26 cm. Rata-rata ukuran pertama kali tertangkap lebih besar dbandingkan dengan ukuran pertama kali matang gonad sehingga ikan lencam di Perairan Bangka masih dapat mempertahankan keseimbangan stok dalam suatu populasi.